Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Berbasis Scramble terhadap Motivasi dan Hasil Belajar Siswa SMA Kristen GPID Palu - Mbosisi, Sifra Bertin; Mustapa, Kasmudin; Ratman, Ratman (Universitas Tadulako, 2018)
This study aimed to determine the effect of the cooperative learning model type teams scramble tournament games based scramble on motivation and learning outcomes students SMA Kristen GPID Palu. The population in this study were all students of class X. The research sample was students (n = 25) of class Xa as a control class and students (n= 24) of class Xb as an experiment class. The testing of student’s learning outcomes data was using the statistical analysis t-test of the two parties and the testing of student’s' motivation using the questionnaire data used a descriptive analysis. The average score of student’s learning outcomes of the experiment class (X1) was 52.83 with a standard deviation of 11.97 and the control class (X2) was 48.12 with a standard deviation of 11.37. Based on the statistical analysis of the hypothesis by t-test two parties, it was obtained that –ttable ≤ tcalculation ³ +ttable (tcalculation = 2.09 and ttable = 2.02) with a significance level a = 0.05 and degrees of freedom = 47, then H0 was rejected and Ha was accepted, therefore it can be said that there is a difference in student’s learning outcomes using cooperative learning model type teams tournament games based scramble. The results of the data analysis of student motivation indicated that the percentage value for the experimental class was 83.4% and for the control class was 81.21% and both were on the agrees attitude with the positive category, so it can be concluded that there is an influence of the cooperative learning model type teams scramble tournament games based scramble on motivation and learning outcomes of students SMA Kristen GPID Palu.